2019
DOI: 10.33086/jhs.v12i02.887
|View full text |Cite
|
Sign up to set email alerts
|

Preceptorship Method to the Achievement of New Nurse Competencies at Rumah Sakit Islam Surabaya Jemursari

Abstract: Competency issues and the lack of implementation of an orientation program with the preceptorship method are problems and require solutions / solutions. The purpose of the study explained the influence of the preceptorship method to the achievement of new nursecompetencies. The design of this study used quasyexperiment by conducting the pre-test and post-test stages in the treatment and control groups. The design of the analysis variable was obtained by twenty new nurses from different units in RSIS Jemursari … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Bentuk komunikasi dan evaluasi antara Preceptor dan Manajer Keperawatan, serta Preceptor dengan Preceptee dapat didokumentasikan kedalam logbook Preceptee yang dapat dievaluasi diakhir kegiatan orientasi (Kurniawan et al, 2019). Pelaksanaan modul Preceptorship dapat meningkatkan kompetensi perawat dalam memberikan asuhan keperawatan 12 kompetensi dasar (Yuliartiningsih et al, 2019). Namun, seringkali kegiatan Preceptorship tidak terdokumentasikan dengan baik.…”
Section: Pendahuluanunclassified
“…Bentuk komunikasi dan evaluasi antara Preceptor dan Manajer Keperawatan, serta Preceptor dengan Preceptee dapat didokumentasikan kedalam logbook Preceptee yang dapat dievaluasi diakhir kegiatan orientasi (Kurniawan et al, 2019). Pelaksanaan modul Preceptorship dapat meningkatkan kompetensi perawat dalam memberikan asuhan keperawatan 12 kompetensi dasar (Yuliartiningsih et al, 2019). Namun, seringkali kegiatan Preceptorship tidak terdokumentasikan dengan baik.…”
Section: Pendahuluanunclassified
“…Caring requires competence, the ability to care for, care appropriately and adequately, and we have the freedom to learn and the opportunity to practice in the nursing profession (7) Caring theory according to (7) (8) with the title Preceptorship Method to The Achievement Of New Nurse Competencies At Jemur Sari Hospital Surabaya stated that there were problems/difficulties working for new nurses in providing nursing care to patients according to their career paths. This is overcome by an orientation that is considered appropriate to provide learning for new nurses because it emphasizes task performance and its implementation using the preceptorship method (9) Research conducted by (10) entitled Application of the Preceptorship Method in Orientation Activities for New Nurses at the Hemodialysis Unit at the Hospital, it was found that there were several obstacles in the application of the preceptorship method to new nurses at the Hemodialysis Unit, in the form of technical guidance implementation, comparison of the number of preceptors with new nurses, fulfilling the qualifications as preceptors, and standardization to evaluate preceptors as well as to increase the competence of new nurses produced after undergoing an orientation period.…”
Section: Introductionmentioning
confidence: 99%